Cholangiocarcinoma: what are the options in all comers and how has the advent of molecular profiling opened the way to personalised medicine ?. (January 2023) - Roth, Gael S.; Neuzillet, Cindy; Sarabi, Matthieu; Edeline, Julien; Malka, David; Lièvre, Astrid
Abstract: Cholangiocarcinoma is a deadly cancer comprising very heterogenous subtypes with a limited therapeutic arsenal in all comers. However, recent significant advances were made with immunotherapy in the first-line treatment of advanced cholangiocarcinoma, with the addition of durvalumab to cisplatin–gemcitabine chemotherapy showing a survival benefit. In the second line setting, only FOLFOX (5FU/folinic acid-oxaliplatin) is validated by a phase 3 trial, yet with a very modest benefit on survival; new options using 5FU with nanoliposomal-irinotecan may emerge in the next few years. The advent of molecular profiling in advanced cholangiocarcinoma in the last decade revealed frequent targetable alterations such as IDH1 mutations, FGFR2 fusions or rearrangements, HER2 amplification, BRAF V600E mutation and others. This strategy opened the way to personalised medicine for patients which are still fit after first-line treatment and the use of targeted inhibitors in first line constitutes a huge challenge with many ongoing trials to improve patients' care. This review exposes the recent clinical trial findings in non-molecularly selected advanced cholangiocarcinoma, offers a focus on how systematic molecular screening should be structured to allow patients to access to personalised medicine, and details which are the therapeutic options accessible in case of actionable alteration. Highlights: CISGEM-durvalumab is a new standard in advanced cholangiocarcinoma in first line. Actionable alterations are present in up to 40–50% of patients, especially in iCCA. Molecular profiling should be proposed to every ECOG 0–1 patients from the diagnosis. Molecular profiling should integrate DNA and RNA next-generation sequencing techniques.